"كيفية إعداد الميزانية المحاسبية والجبائية لدى مكتب محاسب معتمد" - حنان, سناقرية; فلة, مسيعيد; عيادي, سلسبيل (unuversity of eloued- جامعة الوادي, 2023)
"الملخص: نستطيع قول ان أهم ما تطرقنا اليه في بحثنا هذا هو مبحث الاول ماهية ميزانية محاسبية ومن خلال عدة تعاريف توصلنا الى أنها وثيقة مالية ختامية تقوم على أساس عرض صافي ذمة المؤسسة من ثم أشرنا الى بنود ميزانية المحاسبية التي تتكون من الاصول التي هي ممتلكات مادية ومعنوية للمؤسسة وتنقسم الى أصول جارية واصول غير جارية وخصوم التي تنقسم الى رؤوس الأموال الخاصة و خصوم جارية وغير جارية ، ثم أشرنا الى شكل ميزانية ومميزاتها . ثم أشرنا في المبحث الثاني الى تعريف النتيجة جبائية ووصلنا الى أنها هي نفسها مستمدة من نتيجة محاسبية بعد إجراء بعض تصحيحات مع اعادة خصم رسوم معينة وأشرنا الى العناصر المكونة للنتيجة الجبائية ومن ثم الى اهم الطرق التي تحدد النتيجة الجبائية. أما بالنسبة للجانب التطبيقي فعرفنا مكتب المحاسب بصفة عامة ونشأة مكتب المحاسب المعتمد ومحافظ الحسابات الدكتور عوادي مصطفى بصفة خاصة، ومن ثم سلطنا الضوء على مهام المحاسب المعتمد وشروط تعينه، وقمنا بانجاز هيكل تنظيمي لمكتب الأستاذ عوادي مصطفى وأخيرا قمنا بتطبيق الجانب النظري والمتمثل في انجاز الميزانية المحاسبية والنتيجة الجبائية." "Summary: We can say that the most important thing we discussed in this research is the first topic, what is an accounting budget and through several Definitions We have come to the conclusion that it is a final financial document based on the presentation of the net liabilities of the institution, and then we referred to Accounting budget items that consist of assets that are tangible and intangible property of the institution and are divided into assets Current and non-current assets and liabilities, which are divided into private capital and current and non-current liabilities. Then we referred to the form of the budget and its features. Then, in the second topic, we referred to the definition of the tax result, and we reached that it is The same is derived from the accounting result after making some corrections with the re-deduction of certain fees we have indicated The constituent elements of the tax result and then to the most important methods that determine the tax result. As for the practical side, we knew the accountant's office in general and the establishment of the certified accountant and governor's office Accounts Dr. Awadi Mustafa in particular, and then we shed light on the tasks of the certified accountant And the conditions for his appointment, and we completed an organizational structure for the office of Professor Awadi Mustafa, and finally we implemented the aspect Theoretical, which is the completion of the accounting budget and the tax result."
Keywords: الميزانية المحاسبية - الجبائية - مكتب محاسب معتمد; Accounting budget - tax - certified accountant office